Diversidade e vulnerabilidade de insetos aquáticos em paisagens produtivas - Almeida, Mirian Cristina de (2014)
Loss and habitat fragmentation at the landscape scale, the land use and local integrity of habitats (e.g. riparian forests), associated with the social structure of rural lands are factors that can determine the loss of species. These could be greater where of landscapes is homogenized by the same type of land use, such as in agricultural areas. This has important consequences and could be determine that Conservation Biology practices are not based only on Protected Areas. These approaches applied to aquatic insects occurring in Cerrado of Goiás state show that endangered species of Odonata, distributed in the central and south region presented a historical habitat loss of 76%. Regional assessment according to the criteria of the IUCN, a total of 34.8% of species would be in some category of threat, these 71.5% were Critically Endangered, 22,8% Endangered and 4.9% would be vulnerable. Local environmental variables, spatial structure of habitat and matrix in buffers of 250 meters and habitat spatial structure and matrix in the landscapes of 25 by 25 kilometers explained the local richness of Odonata adults in streams. Richness decreases with increase in pasture in the 250 meters buffers and crop in the landscape and increases with the opening canopy. For Ephemeroptera, Plecoptera and Trichoptera (EPT) immature, richness increases with increasing riparian forest 250 meters buffers, with the opening of canopy and the average conductivity of the water. When we consider the habitat integrity (riparian) associated with the structure of rural property around protected areas, the integrity of riparian vegetation as measured by NDVI was lower in the Buffer Zone of sustainable protect areas associated with small farms. The area of the property dedicated to the cultivation and cattle size has direct impacts to lower NDVI values.